Nonm Adiabatic Catalytic Combustion Of carbon Monoxide Using Flow Reversal - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
An experimental study of non-adiabatic fixed bed reactor for controlling CO gas has been made under flow reversal operation. Temperature measurements have been made within the catalyst and packing beds. The influence of the operating parameters upon the shape of temperature profiles, conversion and heat removal were studied. The experiments showed that the maximum measured reactor temperature and heat removal are rather insensitive to changes in cycle duration